The Urgency of the Problem of Customary Criminal Execution in the Architecture of the Integrated Criminal Justice System after Law No. 1 of 2023 - Yenny Febrianty; Nadya Restu Ryendra; Rindiana Larasati (JURNAL AKTA, 2025)
The New Indonesian Criminal Code (Law No. 1 of 2023) formally recognizes customary criminal law (living law), yet this development generates a fundamental paradox between legal formalization and the absence of procedural mechanisms. The urgency of this issue arises from the inconsistency between the recognition of customary sanctions and the Criminal Procedure Code (KUHAP), which designates the Prosecutor as the sole authority responsible for executing criminal judgments. In practice, the Prosecutor lacks the cultural competence and institutional capacity to implement spiritual and restorative customary sanctions, which traditionally fall under the authority of Customary Leaders. This misalignment between legal authority and practical competence creates an executorial crisis, rendering sentences in the form of “fulfillment of customary obligations” potentially non-executable. Using normative legal research methods and analysis of primary and secondary legal materials, this study finds that the absence of KUHAP reform accompanying the New KUHP exacerbates legal uncertainty. As a result, non-executable judgments are likely to increase, undermining judicial authority and weakening the functional position of customary law within the national criminal justice system.